"Bottle Brush Sign"—Spinal Meningeal Disease on 18F-FDG PET-CT Scan. (September 2016) - Riaz, Saima; Naz, Fozia; Bashir, Humayun; Niazi, Imran Khalid
Abstract : Abstract: A 30-year-old man with a history of stage IV AE diffuse large cell lymphoma of left proximal humerus presented with new onset lower limb weakness at completion of chemotherapy. The 18 F-FDG PET-CT scan showed increased intraspinal uptake from T12 to S1 vertebrae with unique "bottle brush" appearance in keeping with spinal meningeal disease. The leptomeningeal disease was further confirmed on correlative MRI scan.